Users’ Perception on RTGS Service: A Primary Study (Trinity Journal of Management, IT & Media (TJMITM), 2015)
The growth of IT and its remarkable application to banking and financial  sector has greatly facilitated the growth of retail banking to a very large  extent. Banking services are now tilting to “Anywhere Any time bank ing” aspect. In addition to websites they have introduced ATMs, Internet  banking, mobile banking, phone banking, ECS, NEFT, and RTGS etc. in  a big way by computerizing and networking their branches. RTGS (Real  Time Gross Settlement) actually uses the Internet as the delivery chan nel to conduct various banking activities like transferring funds, paying  bills, paying mortgages and purchasing financial instruments etc. The  objective of the proposed paper is to determine the users’ perception on  RTGS service. The impact of demographic variables is also highlighted  in the paper. To achieve the objective of the study primary data is collect ed through a structured questionnaire from public, private and foreign  banks customer using RTGS services. In total 750 respondents were sur veyed from Delhi and four administrative divisions of Haryana state. The  Collected primary data was analyzed with the help of various statistical  techniques such as frequency distribution, mean and standard Deviation.  To test the hypotheses formulated in the present paper t test and ANOVA  are used. The findings of the study concluded that convenience and comfort to use,  Quality of transaction, Information and procedure are Response of em ployees/assistance are the major factors which satisfied the users while  using RTGS Facility. The study provides meaningful direction to bank  managers and decision maker to improve their service quality for higher  customer satisfaction.
Keywords: RTGS; Perception; IT Etc